Pembangunan Jaringan Transportasi di Lampung (1859 -1927) - Gregorius Andika Ariwibowo; Hary Ganjar Budiman; Dana Listiana (Badan Riset dan Inovasi Nasional (BRIN), 2023)
The development of transportation networks has been an important factor in accelerating economic and trade progress in Lampung and southern Sumatra since the second decade of the 20th century. The development of transportation facilities has changed the centers of economic activity and settlements in the Lampung region from being centered around rivers to roads and railways. This article discusses the development of transport networks to support the changes in the Lampung region from the mid-19th century to the third decade of the 20th century. This study also explains the development of transport facilities in creating trans Java-Sumatra economic integration during the colonial period. This study aimed to reconstruct the financial history and transport networks of the Lampung region. This study provides a perspective on forming the trans-Sumatra transport network that made Lampung known as the